2020
DOI: 10.23939/chcht14.02.161
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide/Copper/Carbon Composites for the Photocatalytic Degradation of Phenol

Abstract: The incorporation of titanium dioxide and copper onto activated carbon for phenol removal was evaluated. Based on catalyst contents and phenol degradation, four composites were selected and characterized. The results showed that both adsorption and photocatalytic activities were influenced by the presence and arrangement of the catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…where α is the absorption coefficient, A is the constant. 20 In addition, the electrons lifted in the oxygen vacancies can be interacted with adjacent Ti 4+ to produce the Ti 3+ defect species. As a result, shallow donor levels for Ti +3 defect are formed below the conduction band, which also attributes to absorption of visible light.…”
Section: Uv-vis Diffused Reflectance Spectramentioning
confidence: 99%
“…where α is the absorption coefficient, A is the constant. 20 In addition, the electrons lifted in the oxygen vacancies can be interacted with adjacent Ti 4+ to produce the Ti 3+ defect species. As a result, shallow donor levels for Ti +3 defect are formed below the conduction band, which also attributes to absorption of visible light.…”
Section: Uv-vis Diffused Reflectance Spectramentioning
confidence: 99%
“…7 A few studies indicated that solar light triggering the photodegradation of plastic materials, possibly leading to structural defects, 8 surface oxidation, 9 generation of persistent free radicals 10 and nanoparticles. 11 Compared with many studies concerned with the photodegradation of environmental pollutants, 12,13 few studies were performed on the degradation of plastics, for instance, polyethylene plastics biologic-photocatalytic degradation by Zalerion maritimum 14 and nanomaterials like N-doped TiO 2 , [15][16][17][18][19] titania nanotubes, 20 Pt/ZnO, 21 ZnO. 22 In this paper, MgAl 2 O 4 nanoparticles were synthesized via solid-state method and were used as catalysts for the photodegradation of polyethylene plastics under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Another attractive type of process is based on the photocatalytic generation of •OH with ultraviolet and visible radiation. In this sense, a great variety of solid semiconductors (suspended or supported) were proposed for water and wastewater treatment by heterogeneous photocatalysis [31][32][33][34][35][36]. To evaluate the efficiency of AOPs, the decrease in the concentration of a target pollutant, the chemical oxygen demand (COD) and the total organic carbon (TOC) are generally measured.…”
Section: Introductionmentioning
confidence: 99%